EFFECT OF NATURAL AND SYNTHETIC POLYMERS ON THE PROPERTIES OF CANDESARTAN CILEXETIL MATRIX TABLET PREPARED BY DRY GRANULATION - Salih, Omar S; Nief, Roaa A (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of this study is to develop a controlled release matrix tablet of candesartan cilexetil to reduce the frequency of administration, enhance bioavailability and improve patient compliance; a once daily sustained release formulation of candesartan cilexetil is desirable. Methods: The prepared tablets from F1 to F24 were evaluated with different evaluation parameters like weight variation, drug content, friability, hardness, thickness and swelling ability. In vitro release for all formulas were studied depends on the type and amount of each polymer, i.e. (16 mg, 32 mg and 48 mg) respectively beside to the combination effect of polymers on the release of the drug from the tablet. Results: In vitro release showed that formula 13 had the faster release (100% after 4 h) which contained acacia (1:1) and the lowest sustain release was showed for F7 (73% after 8 h) which contained HPMC K100M (1:1). Formula 1 was an 89 % release after 8 h which contain eudragit RS100; F4 was a 100 % release after 5 h which contain Na CMC, F10 was a 100% after 8 h which contain xanthan gum and F16 was a 100 % release after 5 h which contain tragacanth polymer. Formula 9 had a lower release than F7 and F8 respectively. Formula 7 can be used for sustain oral drug delivery of candesartan cilexetil while Formula 13 can be used in contrary as fast release tablets for faster response. Conclusion: Controlled drug delivery system is promising for less dosing and higher patient compliance. Keywords: Angiotensin II receptor antagonist, Hypertension, Matrix system, Control release.